2012
DOI: 10.4049/jimmunol.1103760
|View full text |Cite
|
Sign up to set email alerts
|

Complement Protein C1q Directs Macrophage Polarization and Limits Inflammasome Activity during the Uptake of Apoptotic Cells

Abstract: Deficiency in C1q, the recognition component of the classical complement cascade and a pattern recognition receptor involved in apoptotic cell clearance, leads to lupus-like auto-immune diseases characterized by auto-antibodies to self proteins and aberrant innate immune cell activation likely due to impaired clearance of apoptotic cells. Here, we developed an autologous system using primary human lymphocytes and monocyte-derived macrophages (HMDMs) to characterize the effect of C1q on macrophage gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
199
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(216 citation statements)
references
References 58 publications
16
199
0
1
Order By: Relevance
“…However, in accordance with previous reports (18,21), imC1q significantly downregulated LPS-induced secretion of proinflammatory cytokines, such as IL-1b, IL-6, and TNF-a, compared with HSA alone (IL-1b/IL-6: p = 0.031, TNF-a: p = 0.0435) ( Fig. 2A-C, upper panels).…”
Section: Anti-c1q Induce a Proinflammatory Cytokine Response In Hmdmssupporting
confidence: 79%
See 2 more Smart Citations
“…However, in accordance with previous reports (18,21), imC1q significantly downregulated LPS-induced secretion of proinflammatory cytokines, such as IL-1b, IL-6, and TNF-a, compared with HSA alone (IL-1b/IL-6: p = 0.031, TNF-a: p = 0.0435) ( Fig. 2A-C, upper panels).…”
Section: Anti-c1q Induce a Proinflammatory Cytokine Response In Hmdmssupporting
confidence: 79%
“…Additionally, studies from different research groups demonstrated that C1q enhances the uptake of apoptotic cell material, as well as skews the cytokine profile released by phagocytic cells toward a less inflammatory response during phagocytosis (17)(18)(19)(20). During the uptake of early and late apoptotic cells, C1q exerted a potent inhibitory effect on macrophage-mediated inflammation (21). These data suggest that C1q is crucial in limiting inflammation during the uptake of apoptotic cells.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…C1q is known, however, to be a multifunctional macromolecule with some inherent functions independent of its association with C1r and C1s such as enhancing clearance of apoptotic cells by phagocytic cells (including microglia) and modulating cytokine production to limit inflammation (2)(3)(4). In addition, synthesis of the complement protein C1q has been found upregulated in the brain in response to a variety of neuronal injuries, including models of AD (1,(5)(6)(7).…”
Section: Complement Protein C1q Is Induced In the Brain In Response Tmentioning
confidence: 99%
“…Our results support the theory, that C1q has an important role in the maintenance of immune tolerance by clearing apoptotic and self-antigens. C1q has an important ability to recognize altered or exposed structures of self thereby leading to their efficient clearance by phagocytes without lysis and inflammation (22). Direct binding of C1q may occur to various structures, such as to phospholipids or vimentin exposed by vascular endothelia during tissue damage (23).…”
Section: Discussionmentioning
confidence: 99%